If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 64 = -4(6p + 2) Reorder the terms: 64 = -4(2 + 6p) 64 = (2 * -4 + 6p * -4) 64 = (-8 + -24p) Solving 64 = -8 + -24p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '24p' to each side of the equation. 64 + 24p = -8 + -24p + 24p Combine like terms: -24p + 24p = 0 64 + 24p = -8 + 0 64 + 24p = -8 Add '-64' to each side of the equation. 64 + -64 + 24p = -8 + -64 Combine like terms: 64 + -64 = 0 0 + 24p = -8 + -64 24p = -8 + -64 Combine like terms: -8 + -64 = -72 24p = -72 Divide each side by '24'. p = -3 Simplifying p = -3
| 3x+5-1+3+4x=14 | | (x+3)(x+1)=0 | | 17x=180 | | 10=-2c | | 6(5x+4)(3x-1)=0 | | v+42-3v=-34 | | 9g+8g=17 | | 8[5-3]=0 | | 3[2a-4]=0 | | 2c+a=-3c+44 | | 2z+5+3z=10 | | -5x^2+15x-9=0 | | -3[r+4]=21 | | -5w(w-3)(w+2)=0 | | -3[r+4]=-21 | | 5[q+6]=-20 | | 5[q+6]=20 | | 8x-9=33-4x | | 5x+7=2x-9 | | -3(-4-6x)=84 | | x^3+2x^2+4=0 | | -y+3z=9 | | 12+18x=84 | | 2+18x=84 | | 6x-6x=-2 | | 3x^3-6x^2-45x=0 | | 7k^2+6k-1=0 | | 5-(3n+5)=3-(7n+3) | | 14m+4n-6m+11n= | | 6n^2-14+8=0 | | 3(u-3)=2(x+5) | | [b+5]=2b+3 |